Interorganizational Relations In Marketing Channels - Reve, Torger; Stern, Louis W. (Academy of Management Review, 1979)
In most articles appearing in the organizational behavior journals, little reference is made to the extensive research performed in the marketing field addressing interactions in distribution channels. This article attempts to bring to the fields of sociology and organizational behavior relevant materials from marketing that will improve theories of interorganizational relations.